Effect of mixed TeO2B2O3 glass former in Ho3+/Yb3+-doped glass system: Raman spectroscopy, Judd-Ofelt and luminescence investigations - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2024)
Effect of mixed TeO2B2O3 glass former in Ho3+/Yb3+-doped glass system: Raman spectroscopy, Judd-Ofelt and luminescence investigations by Muhammad Noorazlan Abd Azis